Resistance to ideologies: A study of Melville’s “Bartleby the Scrivener” - Thapa, Bal Bahadur (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5822 Bodhi 2010 4(1): 223-232